Fundamentals of contemporary mass spectrometry - Dass, Chhabil (Wiley-Interscience, 2007)
Mass spectrometry has played a pivotal role in a variety of scientific disciplines. Today it is an integral part of proteomics and drug discovery process. Fundamentals of Contemporary Mass Spectrometry gives readers a concise and authoritative overview of modern mass spectrometry instrumentation, techniques, and applications, including the latest developments. After an introduction to the history of mass spectrometry and the basic underlying concepts, it covers: Instrumentation, including modes of ionization, condensed phase ionization techniques, mass analysis and ion detection, tandem mass spectrometry, and hyphenated separation techniques; Organic and inorganic mass spectrometry; Biological mass spectrometry, including the analysis of proteins and peptides, oligosaccharides, lipids, oligonucleotides, and other biological materials; Applications to quantitative analysis.